2018
DOI: 10.1039/c8cp00487k
|View full text |Cite
|
Sign up to set email alerts
|

Effective computational route towards vibrational optical activity spectra of chiral molecules in aqueous solution

Abstract: We present a computational methodology based on a polarizable Quantum Mechanical (QM)/Molecular Mechanics (MM) approach to accurately compute the Vibrational Optical Activity (VOA) spectra of chiral systems. This approach is applied for the calculation of Infrared (IR), Vibrational Circular Dichroism (VCD), Raman and Raman Optical Activity (ROA) spectra of aqueous solutions of (l)-methyl lactate and (S)-glycidol. Remarkable agreement between calculations and experiments is reported, showing the reliability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 109 publications
(174 reference statements)
1
86
0
Order By: Relevance
“…In general, five models of increasing complexity will be considered: (1) Figure 2 enough to yield a converged spectrum as already pointed out by some of the present authors. [50,51,84,85] The QM/FQ convoluted and averaged spectra for molecules I-VII are reported in Figure 7. Therein the QM/PCM, QM/QM w /PCM, QM/TIP3P, QM/QM w /FQ, and experimental data are also plotted.…”
Section: Excitation Energiesmentioning
confidence: 99%
“…In general, five models of increasing complexity will be considered: (1) Figure 2 enough to yield a converged spectrum as already pointed out by some of the present authors. [50,51,84,85] The QM/FQ convoluted and averaged spectra for molecules I-VII are reported in Figure 7. Therein the QM/PCM, QM/QM w /PCM, QM/TIP3P, QM/QM w /FQ, and experimental data are also plotted.…”
Section: Excitation Energiesmentioning
confidence: 99%
“…[68][69][70][71][72][73][74] GLY, which bears an additional hydroxil group, has been previously studied both theoretically and experimentally. 36,54 In particular, it has been shown that eight different GLY conformers exist in aqueous solution, thus its theoretical modeling is challenging. 36,54,75 GA is an organic acid characterized by the presence of three hydroxil groups linked to the aromatic ring.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…53 Therefore, it appears to be an ideal test-bed for QM/FQFµ. [34][35][36] Thus, the comparison between the two approaches can directly quantify the relevance of fluctuating dipoles in the description of vibrational spectra and report on the performance of the novel QM/FQFµ method. where the PCM is used as third layer and coupled to both QM and FQ portions.Such a similarity means that water molecules explicitly included in snapshots are able to also account for bulk water effects.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations